The criminal offense of abuse of position or trust in business activity and the limits of free economic initiative - Dežman, Zlatko (Lexonomica, 2017)
The criminal offense of abuse of position or trust in business activity within the meaning of the Slovenian Criminal Code is the most common criminal offense against the economy. To adequately assess such an offense it is essential to clarify at the very beginning of the criminal proceedings that all preliminary questions have their origin in the field of civil, corporative and commercial law. In other words, the difficulty of problem solving for such cases in later stages of the process only intensifies, as the decision-making process becomes more and more difficult and can cause delays. And even in cases where the facts are undisputed, the whole issue concentrates primarily around the dispute regarding the issue of material criminal law. The purpose of this paper is to present the abovementioned issues, firstly from a more theoretical perspective on freedom of economic (business) initiative in a postmodern era, followed by a presentation of the criminal law subsystem dealing also with phenomena from the economic subsystem, and lastly by a presentation of the Slovenian Criminal Code in regards to prosecution and adjudication of economic crimes and its difficulties, specifically by using the example of the abovementioned offense.
Keywords: gospodarsko pravo; kazenski pregon; kazniva dejanja; sodišča; zloraba položaja